Integrating Pestle and Swot for Advancing Sustainable Inland Waterway Transportation: Insights from West Java, Indonesia - Ade Ratih Ispandiari; Ibnu Fauzi; Nanda Yustina; Zulfa Qonita (Communications)
The potential and challenges of Inland Waterway Transportation (IWT) in West Java, Indonesia were examined in this research, with a focus on sustainability using the SWOT and PESTLE analyses. Key findings show that IWT provides significant environmental benefits, such as reduced carbon emissions, and supports social equity through affordable and accessible transport. However, challenges include sedimentation, water hyacinth proliferation, poor waste management, infrastructure deficiencies and high investment costs. Overcoming these obstacles requires strategic planning that emphasises centralisation of governance, modernisation of infrastructure, environmental management and integration of technology. The findings provide applicable insights for policymakers and stakeholders to foster sustainable and inclusive transport in West Java.